Indonesia After Covid-19: In The Shadow of Tiktok - A . Zahid; Riza Laely Ikayanti; Nitia Agustini Kala Ayu (Asketik: Jurnal Agama dan Perubahan Sosial, 2023)
This article was born from social conditions as well as a long analysis to see how the new habits of society, especially teenagers after Covid-19, have now been contaminated by an application called 'TikTok.’ This study uses a qualitative literature method, with data obtained through books, articles, and YouTube social media. The result of this research is the blurring of social reality that occurs among teenagers on the issue of existence. Existence in this case is a paradigm shift regarding success in achieving something, today's teenagers think that they can be successful instantly by going 'viral' on TikTok. This application is like a field to spill the expression of its users, for the sake of content, many TikTok users seem to throw away shame and break the boundaries of social norms such as pornography, hate speech, and so on, all of which are menus that are presented and can be found easily on the TikTok application.